التحليل الموقعي لحوادث المرور على طريق ( دهوك – إبراهيم الخليل ) - الدليمي، جمال حامد رشيد (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2017)
تناولت دراسة التحليل الموقعي لحوادث المرور على طريق (دهوك-إبراهيم الخليل) والذي ساهم في تنمية القطاع التجاري وتهدف إلى دراسة واقع حال الشبكة في محافظة دهوك لعام 2014، أذ بلغ مجموع أطوالها (5680/كم) ويعتبر ذلك انعكاسا للمستوي التنموي والنشاط الاقتصادي الذي وصلت اليه منطقة الدراسة وان شبكة الطريق تمثل العصب الحساس للنشاط الاقتصادي وحجر الأساس في تنفيذ العديد من المشاريع الاقتصادية والتنموية في محافظة دهوك ومدي انعكاساتها على الواقع التجاري للإقليم. يهدف البحث للكشف عن أهم المعوقات التي يعاني منها الطريق وتحليل العلاقة بين حجم الحركة المرورية ومدي استيعاب كفاءة الخدمات التي يقدمها وصولا الى الاستخدام الأمثل بغية الحد من وقوع الحوادث المرورية. لقد تبين عن طريق التحليل الكمي للبيانات المتحصلة من الدراسة الميدانية وبيانات الدوائر الحكومية، ان طريق منطقة الدراسة يعتبر من أبرز الطرق كثافة من حيث الحجم المروري خلال أيام العمل والرحلات اليومية إلى المؤسسات الحكومية الخدمية، وان تأثير الحوادث المرورية على كفاءة الطريق كانت نتيجة زيادة أعداد المركبات حيث وصلت إلى (95%) حسب تحليل مصفوفة الارتباط. أما التحليل الموقعي لحوادث طريق (دهوك-إبراهيم الخليل) فقد سجل قضاء دهوك عام 2013 اعلي النسب من الحوادث (39.6) مقارنة مع باقي الاقضية التي تقع على مسار الطريق والسبب الزخم المروري وكثافة حركة المركبات في دهوك كونها تمثل بداية الدخول إلى مركز المدينة، فضلا عن وجود عدة مراكز حيوية ومؤسسات حكومية خدمية اخري، وأخيرا فقد توصل الباحث إلى بعض الاستنتاجات التي من خلالها تم صياغة بعض التوصيات التي يراها الباحث حلول مناسبة مع أسس تخطيطية سليمة يترتب عليها الحد من مشكلة الحوادث المرورية
Addressed by the study of the efficiency of (Dohuk - Zakho) road, which contributed to the development of the commercial sector and aims at the reality of the network in the province of Dohuk in 2014, with a total length of (5680 / km) and this is considered as a reflection of the level of development and economic activity which has been reached in the area, the network represent a sensitive nerve of the economic activity ,and the foundation stone in the implementation of many economic and developmental projects in the province of Dohuk and the extent of its impact on the commercial reality of the territory, also it aims at assessing the efficiency of (Dohuk-Zakho) road and to reveal the most important constrains which the road faces , in addition to analyzing the relationship between the size of the traffic and efficiency of the service it provides ,down to the optimal use. Through the quantitative analysis from the data collected from the filed study and government departments that the road which is the subject of the study considered one of the most prominent road density in terms of traffic volume during the days of work and daily trips to the governmental and service organizations, as for the impact of traffic accidents those were the result of increasing the number of vehicles on the road, as it reached (0.95) by analyzing the correlation matrix. While the site analysis of accidents of the mentioned road resulted that in 2013 Duhok province had the highest level of accidents (39.6%) in accordance with other provinces at the same road and this is due to the traffic rush and the excessive automobile transportation because it represent the entrance to the city center in addition to the presence of the governmental establishments. At last many conclusions were reached and then lead to recommendations which the researcher sees them suitable solutions based on planned base and must lead to the elimination of the traffic accidents
Keywords: حوادث المرور -- طريق دهوك – إبراهيم الخليل -- حوادث الطرق